The The Effectiveness of “Milk Booster” / Galactogogue to Increasing the Breastmilk Production - Virgian, Kharisma (Yayasan Rumah Ilmu Professor, 2022)
Breast milk is the best food for babies from the first beginning of life. Breast milk contains complete nutrients that are needed by babies. The breastfeeding process is a natural phase experienced by a mother. In order to breastfeed well and smoothly, the mother must prepare from the moment of pregnancy. However, sometimes an obstacle occurs in the process of breastfeeding. Thus resulting in the breastfeeding process not running smoothly. Milk booster or Galaktogogue can be consumed by breastfeeding mothers to increase breast milk production. Milk boosters can be in the form of drugs or special supplements that according to research are proven to increase breast milk production. This research is a literature review research to study and analyze the effectiveness of milk booster / galactagogue in increasing breast milk production. As well as reviewing various milk boosters / galactogogue which are proven to increase breast milk production based on evidence-based. This research method is a literature review using Google Scholar, PubMed data and Sciendirect. The results of this study show that milkbooster / galactogogue is effective in increasing breast milk production.